Norwegian wind energy development and bird interactions in the context of environmental impact assessment - Gkillas, Sofoklis (Høgskolen i Bodø, 2010)
Masteroppgave i Energy management - Høgskolen i Bodø, 2010 This is the prelude of the present Master Thesis focused on the Environmental Impact Assessments in the Norwegian wind energy sector. Norway, which has established a target to increase its renewable energy production and energy efficiency to 30 TWh per year in 2016 (compared to 2001), has made a significant turn to wind power development as an efficient alternative energy resource. Nevertheless, green political goals in the past and nature conservation issues, like excessive fatal bird collisions with wind turbines, create cautiousness concerning this wind power venture. Thus, the purpose of this academic research is to discover how Norwegian government is managing to wear thin the negative impacts of wind farms on bird populations; based on a case study on Smøla wind farm, having the largest installed wind power capacity in Norway. These environmental challenges are emphasized and discussed, especially in the context of the Environmental Impact Assessments being carried out. Procedures, guidelines and directives for wind farm licensing and environmental impact assessments are used, discussed, being compared to EU‟s ones and analyzed at length, in order to examine how sustainability in the Norwegian wind power industry can be achieved in an efficient way. In researcher‟s efforts, he attempts to clarify to what extent improvements for mitigating negative bird and wind farm interactions are feasible practically.